TRENDS OF FEMALE LABOUR FORCE PARTICIPATION RATE A SECONDARY ANALYSIS BASED ON PLFS SURVEY - Fasla Rahman K., Prof. Dr Shaheed Ramzan C.P, (EPRA International Journal of Multidisciplinary Research (IJMR), 2024)
Migration shapes human settlement patterns and contributes to economic growth. It also forms human capital. Labour force participation rate, which includes the number of employed individuals, is influenced by gender. Males have a higher share of labor force participation than females. Recent studies show an increasing trend in female labour market employment, with the ILO estimating a 164 million labour force, accounting for half of the century's total migration. This paper examines the changing focus of the labour market, focusing on female labor force trends over seven years, using data from PLFS.The results postulates that the unemployment rate among women had declind from 7 percent to 4 percent and also the rate of female labour force participation had increased creating a positive trend in the area of labour market employment.